2009
DOI: 10.1093/ndt/gfp117
|View full text |Cite
|
Sign up to set email alerts
|

Active vitamin D and its analogue, 22-oxacalcitriol, ameliorate puromycin aminonucleoside-induced nephrosis in rats

Abstract: We demonstrated the breakdown of the vitamin D activation system in podocyte injury, and established a preventative role for vitamin D in podocyte injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
40
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 42 publications
7
40
0
3
Order By: Relevance
“…Previous literature documented that active vitamin D therapy attenuated kidney injury by protecting podocytes (41) and by suppressing renin transcription (42), mesangial proliferation, and interstitial fibrosis (43). Clinical studies have also confirmed its antiproteinuric effects (44).…”
Section: Discussionmentioning
confidence: 92%
“…Previous literature documented that active vitamin D therapy attenuated kidney injury by protecting podocytes (41) and by suppressing renin transcription (42), mesangial proliferation, and interstitial fibrosis (43). Clinical studies have also confirmed its antiproteinuric effects (44).…”
Section: Discussionmentioning
confidence: 92%
“…We hypothesize that the discordant associations of 25(OH)D and 1,25(OH) 2 D with increased albuminuria may be explained by autocrine/paracrine activation of 25(OH)D. This is supported by the fact that 1a-hydroxylase is expressed by various cell types other than tubular epithelial cells, including podocytes, with subsequent local activation of VDRs (44)(45)(46) and circulating levels of 25(OH)D exceeding 1,25(OH) 2 D by approximately 400-fold in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, this anti-proteinuric action of vitamin D analogs is also reported in several clinical studies in patients with chronic renal insufficiency, 19,20,24,30 as well as in other animal models of proteinuric kidney diseases. [31][32][33][34][35] Therefore, it is becoming clear that vitamin D analogs may represent a class of anti-proteinuric agents that are quite effective in alleviating podocyte injury and proteinuria in different circumstances.…”
Section: Discussionmentioning
confidence: 99%